STUDI KOMPARASI PEMIKIRAN ABUL A’LA MAUDUDI DENGAN MUHAMMAD NATSIR TENTANG KONSEP NEGARA ISLAM - Ainur Ropik (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2012)
This paper discusses Abul A'la Maududi comparative thoughts with Muhammad Natsir about the concept of the Islamic State, both in terms of state ideology and form of government. Despite his two live in different social settings, but his political thinking, especially about the Nation of Islam have a lot in common, yet on the other hand there is also the difference, while the striking similarities in the concept of Maududi and M. Natsir are equally wanted the establishment of an Islamic state as a whole. While the difference is the legal basis of each character is like taking Ayat al-Quran and al-Hadith different interpretation. If Maududi considers democracy as shirk, but Natsir considered legitimate democratic origin remains contrary to Islamic law.